Komparasi Pemahaman Peserta Didik antara Sebelum dengan Sesudah Menerapkan Strategi Guided Note Taking - Silvi Yonia Putri; Ainol Ainol; Taufiqurrohman Rifa'i (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
In learning activities, teachers can apply various methods, models, and even strategies to support the achievement of goals. However, it should be noted that not all methods, models, and strategies are suitable and positively impact every learning activity. This research is conducted to determine students' understanding before and after implementing the guided note-taking strategy. In this comparative quantitative study, the researcher will compare students' understanding before and after implementing the guided note-taking strategy. The sample used consists of 21 XIth grade students selected through a random sampling technique. The research data was obtained from the students' comprehension test scores, which were evaluated in three periods: before, one week after, and two weeks after the intervention. One-way ANOVA was used as the statistical technique for measurement. Before and after one week of using the guided note-taking strategy, the findings of the research showed that there were variations in students' comprehension. Similarly, between before and after two weeks, and between after one week and after two weeks of implementing the strategy, students' comprehension increased.